EFFECTIVE INCENTIVE STRATEGIES FOR GENERATION Z EMPLOYEES: AN ANALYSIS OF NEEDS AND PRACTICAL SOLUTIONS - Su Zihao; Kupeshova Saule (World Scientific Reports, 2026)
The relevance of this study is due to the rapid changes in the labor market, as well as an increase in the proportion of generation Z employees who are actively shaping the modern work environment. Representatives of Generation Z have specific values, expectations, and behaviors that differ from previous generations. They are focused on flexibility, rapid career growth, digitalization of processes, work-life balance, as well as meaningful and meaningful activities. In this regard, traditional methods of staff motivation are becoming less effective, which requires the development of new incentive strategies that take into account the characteristics of generation Z. The scientific novelty of the research lies in the systematization and clarification of the key motivational factors characteristic of generation Z in the context of the modern organizational environment. The study also suggests a practice-oriented approach to the formation of a hybrid incentive system that combines tangible and intangible tools with an emphasis on digital and personalized engagement mechanisms. The purpose of the study is to identify and substantiate the most effective incentive strategies for Generation Z employees based on an analysis of their needs and work behavior characteristics.